Intensified follow-up of patients with type 1 diabetes and poor glycaemic control: a multicentre quality improvement collaborative based on data from the Norwegian Diabetes Register for Adults - Jannicke Igland; Marjolein Memelink Iversen; Sverre Sandberg; Magne Rekdal; Siri Carlsen; Tone Vonheim Madsen; John Graham Cooper; Karianne Loevaas; Grethe Åstrøm Ueland; Una Sølvik (BMJ Open Quality)
Background Patients with type 1 diabetes mellitus (T1DM) and poor glycaemic control are at high risk of developing microvascular and macrovascular complications. The aim of this study was to determine if a quality improvement collaborative (QIC) initiated by the Norwegian Diabetes Register for adults (NDR-A) could reduce the proportion of patients with T1DM with poor glycaemic control (defined as glycated haemoglobin (HbA1c)≥75 mmol/mol) and reduce mean HbA1c at participating clinics compared with 14 control clinics.Method Multicentre study with controlled before and after design. Representatives of 13 diabetes outpatient clinics (n=5145 patients with T1DM) in the intervention group attended four project meetings during an 18-month QIC. They were required to identify areas requiring improvement at their clinic and make action plans. Continuous feedback on HbA1c outcomes was provided by NDR-A during the project. In total 4084 patients with type 1 diabetes attended the control clinics.Results Between 2016 and 2019, the overall proportion of patients with T1DM and HbA1c≥75 mmol/mol in the intervention group were reduced from 19.3% to 14.1% (p<0.001). Corresponding proportions in the control group were reduced from 17.3% (2016) to 14.4% (2019) (p<0.001). Between 2016 and 2019, overall mean HbA1c decreased by 2.8 mmol/mol (p<0.001) at intervention clinics compared with 2.3 mmol/mol (p<0.001) at control clinics. After adjusting for the baseline differences in glycaemic control, there were no significant differences in the overall improvement in glycaemic control between intervention and control clinics.Conclusions The registry linked QIC did not result in a significantly greater improvement in glycaemic control at intervention clinics compared with control clinics. However, there has been a sustained improvement in glycaemic control and importantly a significant reduction in the proportion of patients with poor glycaemic control at both intervention and control clinics during and after the QIC time frame. It is possible that some of this improvement may be due to a spillover effect from the QIC.